The Effect of Time Token Technique towards Students’ Speaking Skill at Science Class of Senior High School 1 Pariaman - Muhammad Kristiawan; Riaci Bertty Parlian; Indra Johari (Institut Agama Islam Negeri Imam Bonjol Padang, 2016)
This research aims at finding out the effect of time token technique towards students’ speaking skill. This research was experiment. The population in this research was students at grade XI of High School 1 Pariaman consist of 170 students. Cluster random sampling was used to determine two classes which consist of 68 students. MIPA1 was treated through time token technique while MIPA5 was treated through debate technique. The result of the study showed that the mean score of experimental class was 78.41 with standard deviation 5.39 and mean score of control class was 75.71 with standard deviation 5.35. In order to prove the hypothesis, the t-test score of experimental class was compared with t-table score. It showed that the result of t-test of the experimental class was 2.094 while the result of t-table at a level of significance with α = 0.05 was 1.997. It indicated that the t-score of experimental class was higher than t-table, 2.094 1.997. It means Ho is rejected and Hi was accepted. It was clear that time token technique gave significance effect towards students’ speaking skill.